Language Policy in Communication Between Students at UPN “Veteran” East Java Campus - Aufa Hanif Zakiyah; Firyal Syahirah; Shabrina Fadilah Ghaisani; Revina Ramadhani Putri Sembada; Teuku M. Amri Yahya Kusnan (KIRANA : Social Science Journal, 2026)
Politeness in communication is an important aspect that affects social interaction among students, especially on campus. This study aims to analyse the form and level of politeness in communication among students at the National Development University "Veteran" in East Java. A qualitative approach was used to understand politeness through observation and in-depth interviews with students from various faculties. The results of the study show that politeness in student communication is reflected in language choice, the use of polite greetings, and attention to different social contexts. Factors that affect the level of politeness include cultural background, friendship environment, and the influence of student organizations. This research emphasizes the importance of increasing students' awareness of communication politeness to create a harmonious, conducive campus environment for intellectual and social development.